Адсорбційна іммобілізація хітозану на поверхні кремнезему - Кулик, Т.В.; Паляниця, Б.Б.; Бородавка, Т.В.; Чуйко, О.О. (Видавничий дім "Академперіодика" НАН України, 2007)
The adsorptive modifying of silica by chitosan is carried out. The isotherm of adsorption and the value of the limiting adsorption of chitosan on the surface of fumed silica are found. The desorption of chitosan from the surface of fumed silica has been investigated. The optimum conditions for obtaining a chitosan-silica nanosorbent are determined. The scheme of thermal decomposition of chitosan and chitosan adsorbed on the silica surface is offered. It has been shown that, in the thermolysis of chitosan adsorbed by the silica surface, the low-temperature maximum appears on thermodesorption curves which corresponds to the thermolysis of segments directly connected with the silica surface.